Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus - Delgado-Blas, Víctor Hugo; Díaz-Díaz, Oscar (Zootaxa, 2016)
Available type material of Dispio uncinata Hartman, 1951 and D. mororoi Gibbs, 1971, as well as newly collected material from Venezuela and material deposited in the Los Angeles County Museum of Natural History, was examined. Several important differences were found between D. uncinata, D. mororoi, the new material deposited in the museum and the newly collected material from Venezuela, Panama and California. Dispio uncinata and D. mororoi are redescribed and five new species are also identified and described: D. anauncinata sp. nov., D. lenislamellata sp. nov., and D. longibranchiata sp. nov. are from Southern California, D. panamensis sp. nov. from Panama, and D. bescanzae sp. nov. from Venezuela. Morphological differences between species were recorded, particularly in reference to the shape of prostomium, and caruncle, size of peristomium, shape of notopodial and neuropodial postchaetal lamellae, branchiae from anterior chaetigers fused completely or partially to the notopodial lamellae, presence or abscent of accessory branchial pairs, structure of notopodial and neuropodial chaetae, notopodial and neuropodial lamellae overlapping or touching and other consistent characters. Results of the review of the material from Southern California indicates that D. uncinata is not found in this area of the Pacific, and we recommend that the wide distribution of this species should be taken with caution especially for those distant records from the type locality. A key to all species of Dispio is provided.